FEMTOSECOND LASER IN CATARACT SURGERY - N. P. Pashtaev (Офтальмохирургия, 2017)
The article presents a review of the literature on the history of laser use in cataract surgery, their technical properties, peculiarities of influence on tissue, modern laser units for cataract surgery, experimental and clinical results, evaluation of the efficacy and safety of femtosecond laser-assisted cataract surgery (FLACS). Analysis of publications testifies that FLACS is safe and more effective versus traditional ultrasound phacoemulsification which is proved by a statistically significant increase of clinical, functional and subjective indices of visual system in early and long-term postoperative periods.